(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
Miocene carbonates and marls in the northwestern margin of the Hyblean Plateau (SE Sicily) exhibit considerable thickness variations consistent with synsedimentary tectonism. In the Early-Middle Miocene carbonates (Ragusa Formation) a series of parallel swells dose to the platform edge encouraged the development of a coarse-grained bioclastic facies. The overlying Middle-Late Miocene marls (Tellaro Formation) thin over these seafloor highs and associated mafie Tortonian volcanics are particularly developed along the hinge zones between swells and local sea-floor depressions. The basic extrusives appear to have followed incipient NE-SW fault lines propagated from deeper basement fractures. During the succeeding Messinian these faults were activated to produce horst structures (Vallone Lamia horst, Monte Caratabia horst and Cameme horst). These separate locai NE-SW oriented narrow grabens in which thick Messinian evaporites were deposited, probably connected with the main Centrai Sicilian Basin. Further subacrial deposits and volcanics levelled the Hyblean horst and graben topography prior to the major Early Pliocene marine high-stand. The ensuing transgression covered the study area with a thick pelagic Early Pliocene chalk. Local regressions, the product of Middle Pliocene and Early Pleistocene major tectonic activity along the margins of the plateau, are associated with local unconformities. Final emergence along the margins of the plateau occurred at the close of Early Pleistocene times when the emplacement of the Gela Nappe, from the NE, partly filled the foredeep basin. The withdrawal of the sea from the foredeep occurred shortly afterwards.